ASSESSMENT OF LATE GADOLINIUM ENHANCEMENT IN CARDIAC MRI - Hadji Nikolova, Natasha; Lazareska, Menka; Aliji, Vjolca; Ilievski, Mitko; Daskalov, Dejan; Stojkoski, Aleksandar; Pasoska, Milkica (Journal of Morphological Sciences; Vol 4 No 2 (2021): JMS, 2021)
The aim of this study was to evaluate MRI characteristics of ischemic and non-ischemic cardiomyopathies with late dadolinium enhancement analysis that can provide differentiation between these two cardiomyopathies. Eligible 96 patients, age range from 26 to 71 years, who showed different and overlapping clinical symptoms, ECG andtransthoracic echocardiography findings that needed further evaluation were included in our study for further evaluation with cardiac MRI. Of the evaluated patients, 47 were females and 49 were males. The examinations were performed with MRI Scanner 1,5T Siemens Avanto by using 3 channeledSiemens ECG electrodes with retrospective triggering. With the help of PSIR sequence for late gadolinium enhancement evaluation we differentiated ischemic cardiomyopathy from non-ischemic cardiomyopathy, which is crucial for management of patients with cardiac dysfunction. Of the examined 96 patients, 42 patients were diagnosed with ischemic cardiomyopathy, 51 with non-ischemic cardiomyopathy, and 3 patients had non-conclusive diagnosis. It was found that late gadolinium images in the setting of cardiac MRI were capable of detecting myocardial scars and fibrosis. Moreover, they helped in differentiation between ischemic and non-ischemic cardiomyopathieson the basis of myocardial scar enhancement pattern. Keywords: cardiac magnetic resonance, late gadolinium enhancement, cardiac function, prognosis   https://doi.org/10.55302/JMS2142163hn